2013
DOI: 10.1111/nyas.12116
|View full text |Cite
|
Sign up to set email alerts
|

Application of combined omics platforms to accelerate biomedical discovery in diabesity

Abstract: Diabesity has become a popular term to describe the specific form of diabetes that develops late in life and is associated with obesity. While there is a correlation between diabetes and obesity, the association is not universally predictive. Defining the metabolic characteristics of obesity that lead to diabetes, and how obese individuals who develop diabetes different from those who do not, are important goals. The use of large-scale omics analyses (e.g., metabolomic, proteomic, transcriptomic, and lipidomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
0
22
0
1
Order By: Relevance
“…Furthermore, the relationship that we observe between C3 and preprandial insulin ( Figure 2D) may suggest a predisposition for mitochondrial overload in HEU-A infants. BCAA metabolism via anapleurotic flux into the succinyl CoA pool, if excessive, can overload the tricyclic acid (TCA) cycle resulting in the accumulation of acetyl-CoA (28). The relationship between C3 and insulin ( Figure 2D) may be considered a contributing cause, while the relationship between C2 and insulin ( Figure 2B) may be considered as an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship that we observe between C3 and preprandial insulin ( Figure 2D) may suggest a predisposition for mitochondrial overload in HEU-A infants. BCAA metabolism via anapleurotic flux into the succinyl CoA pool, if excessive, can overload the tricyclic acid (TCA) cycle resulting in the accumulation of acetyl-CoA (28). The relationship between C3 and insulin ( Figure 2D) may be considered a contributing cause, while the relationship between C2 and insulin ( Figure 2B) may be considered as an effect.…”
Section: Discussionmentioning
confidence: 99%
“…New technologies to allow rapid and widespread serum metabolome, or proteome, analysis would also be vital to allow widespread implementation of this approach [125][126][127][128] . Nevertheless, recent work has indicated that understanding alterations in metabolite profiles can provide a high degree of predictive accuracy for insulin resistance 129 .…”
Section: Future Biomarkers Of Insulin Sensitivitymentioning
confidence: 99%
“…However, no study has systematically examined the role of miR-205 in normal urothelial differentiation. Recent advances in various "omics" approaches are employed to gain the knowledge of various cellular functions, pathways, and disease biomarker identification (35)(36)(37)(38). In the present study, we used a multiple-omics approach to investigate the targets of miR-205 in primary cultured urothelial cells.…”
mentioning
confidence: 99%